Från diagnostisering till intersektionalitet: Tendenser inom Strindbergsforskningen 1963–2011 - Lönngren, Ann-Sofie (Tidskrift för litteraturvetenskap, 2011)
From Diagnosis to Intersectionality: Strindberg Research from 1963–2011 This article was written as a sequel to Göran Lindström’s article in Svensk litteraturtidskrift (Swedish Literature Magazine) in 1962, and consists of a qualitative, evaluative survey of research on the Swedish author August Strindberg (1849–1912) during the period 1963–2011. A selection of more or less new sub-fields (such as music, TV, radio, film, prose and poetry) arise within the larger field of research on Strindberg’s life and works during this time. Simultaneously, research on drama, modernity, history and mysticism continues to develop. The field of psychological studies underwent major transformations during this period, as tendencies to diagnose the author shifts to a discussion of the historical production of concepts such as “madness”. This tendency is also visible in the field of biographical research, where the intention to reveal the “truth” about the author gives way to investigations of the “author” as a literary function. Furthermore, the same development could be seen in the field that went through the most rapid and thorough change and expansion, gender studies, where attention shifts from investigating Strindberg’s relationship to women to a discussion of the historical production of norms concerning gender and sexuality. My conclusion was, however, that gender studies as well as the discussion of Strindberg as a national author need to employ a more intersectional approach in the future to further deepen and develop these fields. In 1962, Lindström called for additional pieces to add to the Strindberg-puzzle. In 2011, I ask for further development of the critical meta-perspectives on the great cultural construct known as “Strindberg”.